GAMBARAN PENGETAHUAN REMAJA TENTANG DISMENORE PADA SISWA PUTRI DI MTS NU MRANGGEN KABUPATEN DEMAK - Nafiroh, Defi; Indrawati, Nuke Devi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2013)
ABSTRACT: OVERVIEW OF TEENS KNOWLEDGE ABOUT DYSMENORRHEA FOR FEMALE STUDENT MTS NU MRANGGEN DEMAK REGENCY. Dysmenorrhea is stiffeness or spasms in the lower abdomen that occur before or during menstruation, which force women to take rest or cause declining their work quality and their daily activities. From interviewing 10 female students, there are seven female students who do not really know about Dysmenorrhea, one female student who know enough about Dysmenorrhea and two female students who already know about Dysmenorrhea. It maybe happen because there is no sosialitaion about healthy reproduction education in MTs NU Mranggen Demak regency. Purpose : of this research was to know about Dysmenorrhea understanding from female students of MTs NU Mranggen Demak regency. Method : this research is descriptive research with point time method. Total population consist of 84 female students from class VII, VIII, and IX, then sampling was performed using a stratified sample of 46 female students. Instruments in this study using a questionnaire with 20 deviation and frequency distribution. Results : obtained are the majority of respondens are mid-teens (ages 13-15 years) is 84.8% and the majority of respondens had less knowledge about Dysmenorrhea amounted to 78.3%. Conclusion : the majority of responden had less knowledge about Dysmenorrhea that is equalto 36 female students (78.3%).Keywords : Knowledge, Dysmenorrhea, Female Students of MTs